How and when do markets tip? Lessons from the Battle of the Bund - Estelle Cantillon; Pai-Ling Yin (European Central Bank (ECB), 2007)
In a famous episode of financial history which lasted over eight years, the market for the future on the Bund moved entirely from LIFFE, a London-based derivatives exchange, to DTB, a Frankfurt-based exchange. This paper studies the determinants of the observed dynamics, using a novel panel dataset that contains individual trading firms' membership status at each exchange together with other firms characteristics, and pricing, marketing and product portfolio strategies by each exchange. Our data allows us to distinguish between different explanations for the observed phenomenon. Our results indicate that the main driver was a "market coverage" effect: thanks to the combination its electronic market structure and EU-wide access deregulation, DTB increased the relevant size of the market for exchange members and disproportionately attracted those firms who originally did not exist or used to submit their orders through a broker. Differential liquidity and product portfolio strategies by the exchanges played a secondary role.
Keywords: G21; G28; L13; L43; 330; adoption cost; Bund; electronic trading; Exchange competition; network effect; open outcry; tipping; Derivat; Marktmikrostruktur; Deutschland; Großbritannien